2015
DOI: 10.1017/s0967199415000283
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of l(–)-rhamnose in sea urchin gastrulation. Part II: α-l-Rhamnosidase

Abstract: The sea urchin embryo is recognized as a model system to reveal developmental mechanisms involved in human health and disease. In Part I of this series, six carbohydrates were tested for their effects on gastrulation in embryos of the sea urchin Lytechinus pictus. Only l-rhamnose caused dramatic increases in the numbers of unattached archenterons and exogastrulated archenterons in living, swimming embryos. It was found that at 30 h post-fertilization the l-rhamnose had an unusual inverse dose-dependent effect,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Previously, this laboratory has studied several glycan effects during sea urchin gastrulation using similar assays (Latham et al , 1998, 1999; Khurrum et al , 2004; Coyle-Thompson & Oppenheimer 2005; Razinia et al 2007; Singh et al , 2014; Liang et al , 2015). In the present study α-mannosidase enzyme inhibited proper organization and attachment of the Lytechinus pictus archenteron suggesting the presence of one or all types of α1–2-, α1–3-, or α1–6-linkages.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, this laboratory has studied several glycan effects during sea urchin gastrulation using similar assays (Latham et al , 1998, 1999; Khurrum et al , 2004; Coyle-Thompson & Oppenheimer 2005; Razinia et al 2007; Singh et al , 2014; Liang et al , 2015). In the present study α-mannosidase enzyme inhibited proper organization and attachment of the Lytechinus pictus archenteron suggesting the presence of one or all types of α1–2-, α1–3-, or α1–6-linkages.…”
Section: Discussionmentioning
confidence: 99%
“…Galectins, endogenous carbohydrate-binding proteins present in most metazoan phyla [68] and some multicellular fungi (mushrooms) [69], but in neither unicellular holozoans nor in yeast, may have been involved in the origination of the triploblastic body plan. Interference with galectins leads to the loss of the primitive streak in the early-stage chicken embryo [70], and exogenous administration or degradation of the sugar ligand for a putative endogenous sea urchin lectin dramatically perturbs gastrulation in that organism [71]. Like multilayering, lumen formation and body elongation, triploblasty may thus have arisen ( perhaps more than once) by the mobilization of physical organizational effects by a small number of pre-existing gene products (and perhaps a few novel ones), acting in new contexts.…”
Section: Extracellular Matrices Diploblasty and Triploblastymentioning
confidence: 99%
“…This laboratory has studied the role of carbohydrates in embryonic development and cancer for a half century [1][2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The author of this current work, Steve Oppenheimer, has been recognized by election as Fellow of the American Association for the Advancement of Science (AAAS) primarily for his work in the field of glycobiology. Studies beginning at Johns Hopkins [1] have identified metabolic pathways and specific glycans involved in cellular interactions in the developing sea urchin embryo model [2][3][4][5][6][7] and in cancer cells [1]. A heavily downloaded review was published by this group that covered the fundamentals of glycobiology [8].…”
Section: Introductionmentioning
confidence: 99%